Penyelenggaraan Pos Pembinaan Terpadu Penyakit Tidak Menular Di Wilayah Puskesmas Sungai Piring Kabupaten Indragiri Hilir - Nurlian Nurlian; Zulfan Saam; Agus Alamsyah; Novita Rany; Emy Leonita (Jurnal Kesehatan Komunitas, 2020)
The increasing prevalence of non-communicable disease is a serious threat to development, because it threatens national economic growth. Public Health Center of Sungai Piring area is one of the largest Non-Communicable Disease ofÂ  Integrated Guidance Post (Posbindu PTM) distributions out of 28 Public Healh Centers in Indragiri Hilir regency, however, health screening at Non-Communicable Disease of Integrated Guidance Post (Posbindu PTM) was only 31.1% of the program target in 2019. Through it, early detection of Non-Communicable risk factors could be detected so that the incidence of it in the community could be pressed. The purpose of knowing the trends of input, process and output in implementation of Non-Communicable Disease of Integrated Guidance Post (Posbindu PTM) at Public Health Center of Sungai Piring Area, Indragiri Hilir Regency in 2019. This type of research was qualitative research that used purposive sampling technique. Research informants were the head of Public Health Center, Headman, the village head, the person in charge of the program, officers, cadres and users of Integrated Guidance Post. The Collecting data was interview, observation and documents related with a triangulation analysis of data sources and methods. The result of the research was in terms of input, the role of officers had been optimal, but the roles of cadres and policy makers had not been optimal, limited funding of Health Operational Assistance (BOK) funds and the infrastructure Public Health Center was not optimal. From the process of planning and coaching Non-Communicable Disease of Integrated Guidance Post (Posbindu PTM) had not been optimal, the types of activities were not in accordance with the Integrated Guidance Post concept, follow up the monitoring of risk factors had been carried out by Integrated Guidance Post officers and the basic Integrated Guidance Post criteria phasing. The output of evaluation in implementation of Integrated Guidance Post of Non-Communicable Disease at Public Health Center of Sungai Piring Area in 2019 was seen from the input and process there still obstacles. It should be necessary to increase socialization and support from related sectors to increase the utilization of Non- Communicable Disease of Integrated Guidance Post (Posbindu PTM). Â